Tashi and the phoenix - Fienberg, Anna.; Fienberg, Barbara; Gamble, Kim (Crows Nest, Australia : Allen & Unwin, 2008)
After Tashi's uncle boasts that he has captured "the most dazzling creature in the world," the Warlord demands to see it; and later, when Tashi receives a letter from Princess Sarashina, he must find a way to prevent Sarashina's sister from marrying the evil Khan.
3.5
3-6.
3-6
Keywords: Marriage -- Juvenile fiction; Phoenix (Mythical bird) -- Juvenile fiction; Tashi (Fictitious character) -- Juvenile fiction; Adventure and adventurers -- Fiction; Marriage -- Fiction; Phoenix (Mythical bird) -- Fiction; Storytelling -- Fiction; Tashi (Fictitious character) -- Fiction; Adventure fiction; Marriage -- Fiction; Phoenix (Mythical bird) -- Fiction; Storytelling -- Fiction; Tashi (Fictional character) -- Fiction; Adventure fiction